"Called" To Speak Out: Employee Career Calling and Voice Behavior. (February 2023) - Chen, Jiatian (JT); May, Douglas R.; Schwoerer, Catherine E.; Deeg, Matt
This study is the first one to explore the relation between career calling and employee voice and two potential mediators of this relationship, felt responsibility for constructive change and employee optimism about the future. Surveys from 406 employees of a law enforcement agency in the Midwest U.S. were analyzed using logistic regression and bootstrapping method with Structural Equation Modeling (SEM) to examine support for the hypotheses' main and mediating effects. A behavioral measure was used to capture employees' promotive voice behavior. Results indicated that individuals with stronger career calling were more likely to engage in promotive voice, after controlling for personality, perceptions toward work, and organizational tenure. In addition, career calling was positively associated with both felt responsibility and employee optimism. Finally, felt responsibility for constructive change fully mediated the relationship between career calling and promotive voice. The implications of these findings for researchers and practitioners are discussed.